Arthur and the school pet - Brown, Marc Tolon (New York : Random House, 2003)
D.W. volunteers to take care of the class gerbil during Christmas vacation and finds that he is difficult to keep track of.
"Step into reading sticker books-step 2."
Accelerated Reader AR
Keywords: Gerbils -- Fiction; Pets -- Fiction; Christmas -- Fiction; Vacations -- Fiction; Aardvark -- Fiction